2011
DOI: 10.1149/1.3515073
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Degradation of (La,Sr)MnO[sub 3]∕YSZ Cathodes in Solid Oxide Fuel Cells with Uncoated E-Brite Interconnects

Abstract: Transmission electron microscopy was used to investigate the local chemistry and microstructure of the active cathodes in solid oxide fuel cells operated for 500 h ͑at 700 and 800°C͒ under different electrochemical conditions while exposed to a chromiaforming stainless steel. Several distinct microstructural changes were observed owing to chromium interactions with the ͑La,Sr͒MnO 3 ͑LSM͒-yttria stabilized zirconia ͑YSZ͒ cathode; the nature and magnitude of which depended on the temperature, electrochemical loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
(82 reference statements)
1
9
0
Order By: Relevance
“…Their results imply that the local performance will vary with phase fractions, tortuosity, and connectivity, which would also impact the local electrochemical driving forces for microstructural evolution considered in this work. Clearly, much more research is required to understand how the local electrochemical properties vary within cathodes, especially because degradation events, such as Cr‐poisoning, are known to be correlated with local properties, not average properties …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results imply that the local performance will vary with phase fractions, tortuosity, and connectivity, which would also impact the local electrochemical driving forces for microstructural evolution considered in this work. Clearly, much more research is required to understand how the local electrochemical properties vary within cathodes, especially because degradation events, such as Cr‐poisoning, are known to be correlated with local properties, not average properties …”
Section: Discussionmentioning
confidence: 99%
“…Clearly, much more research is required to understand how the local electrochemical properties vary within cathodes, especially because degradation events, such as Crpoisoning, are known to be correlated with local properties, not average properties. 57,58 The last point of interest here is to discuss the impact of these observations on SOFC activity. While we do observe weak texture in the cathodes, one could reasonably approximate the distributions as isotropic.…”
Section: November 2011mentioning
confidence: 99%
“…Such variations not only impact local cell performance and cell reliability, but can impact negatively the long-term performance if they accelerate degradation phenomenon related to the overpotential. 47,52,54,55,59,60 In other words, heterogeneous cells may also degrade faster than homogeneous cells. To investigate this, an in-house multiphysics model called DREAM-SOFC, 68,69 was used to model the effect that microstructural heterogeneity will have on performance.…”
Section: Impact Of Heterogeneities On Cell Performance Distributions-mentioning
confidence: 99%
“…Summary.-Prior microstructural research with nanoscale resolution of phases in electrodes has successfully characterized and correlated microstructural properties to local electrochemical performance, 47,54,55,59,60 but could not assess variability in microscale properties across devices. This work combined analysis on multiple PFIB-SEM scanned electrode microstructure reconstructions from the same cells, as well as different cells of the same manufacturer, which allowed quantifying heterogeneities over length scale that has not been studied before.…”
Section: Impact Of Heterogeneities On Cell Performance Distributions-mentioning
confidence: 99%
“…Using high resolution TEM, Krumpelt reported that the observed microstructrual degradation and partial decomposition of LSM cathode in the presence of un-coated E-Brite interconnect is most likely related to the high cell overpotential and the presence of Cr species. 20,21 Very different from that observed on the LSM electrode, the chromium deposition on (La,Sr)(Co,Fe)O 3 (LSCF) electrodes occurs predominantly on the surface of the LSCF cathode, forming SrCrO 4 . 8,22 Matsuzaki et al studied the performance of an LSCF electrode/samaria-doped ceria (SDC) electrolyte in the presence of a chromia-forming alloy and found no preferential precipitation of Cr species near the electrode/electrolyte interface.…”
mentioning
confidence: 93%